2009
DOI: 10.1002/bem.20563
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal ELF magnetic fields affect acetylcholinesterase activity in cerebellum synaptosomal membranes

Abstract: The effects of extremely low frequency magnetic fields (ELF-MF) on acetylcholinesterase (AChE) activity of synaptosomal membranes were investigated. Sinusoidal fields with 50 Hz frequency and different amplitudes caused AChE activity to decrease about 27% with a threshold of about 0.74 mT. The decrease in enzymatic activity was independent of the time of permanence in the field and was completely reversible. Identical results were obtained with exposure to static MF of the same amplitudes. Moreover, the inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…5). Although, several papers demonstrated that ELF-EMFs could act on membrane bound enzymes [30,41,43,44], it is possible to presume that the variation in enzymatic activities observed in our studies in response to ELF-EMF exposure, could depend upon the ability of ELF-EMF to stimulate transcription by interacting with DNA, as suggested by Blank and Goodman [3] or by activation of signaling pathways. Our data suggest a possible action of ELF-EMFs on the redox state of cells and thus establish a plausible link between ELF-EMF exposure, the expression and activity of specific enzymes and their kinetic activities.…”
Section: Discussionmentioning
confidence: 72%
“…5). Although, several papers demonstrated that ELF-EMFs could act on membrane bound enzymes [30,41,43,44], it is possible to presume that the variation in enzymatic activities observed in our studies in response to ELF-EMF exposure, could depend upon the ability of ELF-EMF to stimulate transcription by interacting with DNA, as suggested by Blank and Goodman [3] or by activation of signaling pathways. Our data suggest a possible action of ELF-EMFs on the redox state of cells and thus establish a plausible link between ELF-EMF exposure, the expression and activity of specific enzymes and their kinetic activities.…”
Section: Discussionmentioning
confidence: 72%
“…This early insight has been corroborated by recent studies on various transmitter receptors in the brain such as N-methyl-D-aspartate receptors, dopamine and serotonin receptors (e.g. [148][149][150][151]. Some of these more recent studies also reported frequency window effects as well as intensity window effects on the neurodevelopment in the rat (152).…”
Section: Neurological Effects Of Extremely Low Frequency Electromagnementioning
confidence: 69%
“…-dependent pathway, sympathetic nervous system (e.g., BRS and the action of sympathetic agonists or antagonists), and neurohumoral regulatory system (e.g., production and secretion of angiotensin II and aldosterone), as reviewed by Ohkubo et al (2007), McKay et al (2007, and McNamee et al (2009). Overviews of suggested mechanisms of SMF effects on experimental animals (Okano et al 1999Okano and Ohkubo 2001, 2003a, b, 2005a, b, 2007Gmitrov et al 2002;Gmitrov and Ohkubo 2002a, b) and cultured cells (Rosen 1992(Rosen , 1996(Rosen , 2003Takeshige and Sato 1996;Ye et al 2004;Abdelmelek et al 2006;Sirmatel et al 2007;Martino et al 2010;Ravera et al 2010) are illustrated as shown in Fig. 1 for biochemical pathways and Fig.…”
Section: Possible Mechanismsmentioning
confidence: 98%